Safety and efficacy of a feed additive consisting of 25‐hydroxycholecalciferol (produced by Pseudonocardia autotrophica DSM 32858) for all pigs, all poultry for fattening and ornamental birds and other poultry species (Huvepharma NV) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of a feed additive consisting of 25‐hydroxycholecalciferol (produced by Pseudonocardia autotrophica DSM 32858) for all pigs, all poultry for fattening and ornamental birds and other poultry species. The production strain P. autotrophica DSM 32858 is not genetically modified however, uncertainties remain on the possible presence of its viable cells in the final product. Due to the lack of adequate safety data and uncertainty on the presence of nano particles, the FEEDAP Panel cannot conclude on the safety of the additive for the target species and the consumer. The additive was shown not to be irritant to skin or eyes and it is not a skin sensitiser. Considering the low dusting potential of the additive, the FEEDAP Panel concluded that the exposure through inhalation is unlikely. However, the FEEDAP Panel considered that uncertainties remain on genotoxicity and on the possible presence of viable cells of P. autotrophica DSM 32858 in the final product which might have an impact on the safety for the users. The use of the feed additive is considered safe for the environment. The Panel concluded that the additive has a potential to be efficacious under the proposed conditions of use.